OPTIMALISASI MODEL MANAJEMEN KEPEMIMPINAN DALAM UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI SEKOLAH - Sumbawati, Novi Kadewi; Rahim, Abdul; Elvazira, Eda (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to determine the relationship between leadership management in efforts to improve the quality of human resources in schools. The type of this study was associative study which aims to determine the effect of the leadership management on improving the quality of human resources in schools. The type of data used in this study was quantitative data obtained directly from respondents using a questionnaire. The respondents for this study are all human resources educators (teachers) at SDN Kakiang, North Moyo Sub-District, Sumbawa District, totaling 12 people. The data used in this study were processed with SPSS software for analysis using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determinant testing (R2). The results of this study showed that the leadership management had a positive and significant effect on the quality of human resources in schools. The ability of leadership management to influence the quality of human resources in schools was 28.7%, while the remaining of 71.3% was influenced by other factors not examined in this study, such as curriculum factors, educational policies, educational facilities, technology applications and communication in education.